The Effect of the Spelling Bees Game to Elevate Students' Vocabulary - Mahfuzh, Muhammad Rifqi; Sujarwati, Iis; Rianyansa, Ari Andre (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Vocabulary mastery is an essential aspect of improving students’ English proficiency, especially for beginner learners who frequently experience challenges in remembering and applying new vocabulary appropriately. Consequently, teachers need to implement creative and interactive learning methods that can enhance students’ motivation as well as their vocabulary development. One teaching technique that may support this objective is the Spelling Bee game, since it provides enjoyable and competitive learning activities that encourage students to practice vocabulary actively. This research was conducted to investigate the effectiveness of the Spelling Bee game in vocabulary instruction. The study applied a pre-experimental method, which is categorized as one of the most basic forms of experimental research. In this approach, a single group received a treatment and the outcomes were observed to determine whether meaningful changes occurred. The research used a one-group pre-test and post-test design. The participants were students from the Beginner A class at Ganesa English Course, selected through purposive sampling. Data were obtained from pre-test and post-test results and analyzed statistically using SPSS software. The statistical analysis from both the paired sample test and t-test showed similar findings. The results revealed a standard error mean of 2.305, a standard deviation of 10.310, and an average difference of -30.000 between pre-test and post-test scores. The maximum difference obtained was -32.174, while the minimum difference was -41.825. In addition, the t-test score reached -16.048 with a significance value of 0.000 at a degree of freedom (df) of 19. These findings indicate that students’ vocabulary achievement improved significantly after being taught through the Spelling Bee game. Therefore, the study concludes that the Spelling Bee game is an effective method for enhancing vocabulary learning among beginner students at Ganesa English Course